Peran Persepsi Kualitas Memediasi Pengaruh Kesesuaian Harga dan Ulasan Pembeli terhadap Keputusan Pembelian Online: Studi pada Produk Aksesori di Shopee Aydeestuff - Ni Nyoman Ayu Sintya Dewi; I Gst. Ngurah Jaya Agung Widagda K (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid growth of e-commerce and marketplaces has influenced consumer purchasing behavior, making the understanding of factors affecting purchase decisions on digital platforms crucial for SMEs. This study aims to analyze the mediating role of perceived quality in the relationship between price suitability and buyer reviews on online purchase decisions for accessory products on Shopee Aydeestuff. Using a quantitative approach and purposive sampling method, data were collected from 100 respondents through a questionnaire distributed via Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that price suitability and buyer reviews significantly influence perceived quality, which in turn affects online purchase decisions. While price suitability positively influences purchase decisions, buyer reviews do not have a direct significant effect. This study highlights the importance of perceived quality as a mediating variable, both in the relationship between price suitability and purchase decisions, as well as between buyer reviews and purchase decisions. Theoretically, this study extends the application of the Stimulus-Organism-Response (SOR) theory by demonstrating how stimuli (price suitability and buyer reviews) are processed by the organism (perceived quality) to trigger a response (online purchase decision).